PENGARUH FASILITAS BELAJAR DAN KOMUNIKASI KELUARGA TERHADAP MOTIVASI BELAJAR SISWA TINGKAT MENENGAH ATAS DAN KEJURUAN SE - KECAMATAN BUNTU PEPASAN - Johanis Martoguhun; Mesta Limbong; Hotmaulina Sihotang (Jurnal Manajemen Pendidikan, 2022)
The purpose of this study was to determine how much influence learning facilities and family communication have on the learning motivation of upper secondary level students in Buntu Pepasan District. In this study the approach used was a quantitative approach. The sampling technique used purposive sampling technique. The number of samples was 62 people. Data collection techniques were carried out by distributing questionnaires directly to the research site. Instrument testing and data analysis were carried out with the help of SPSS Version 25. In testing the hypothesis, a partial test was carried out with the "t" test, obtained a significant value for the independent variable on the dependent variable, namely learning facilities (X1) of 0.009 <0.05 and family communication (X2) of 0.000 < 0.05. on student learning motivation is 0.384 or 38.4%., the influence of family communication on student learning motivation is 0.208 or 20.8%. The large effect of variables X1 and X2 on variable Y is 0.325 or 32.5%. This influence still needs to be improved by increasing the provision of adequate learning facilities at school and at home as well as increasing communication from the family as a provider of support and enthusiasm for learning to high school students throughout Buntu Pepasan District.